Evaluation of normal measurements of fourth ventricle by computed tomography - Kalathuru Uhasai; Deepti Nayak; Anil Kumar Sakalecha; Chaithanya A; Buchipudi Sandeep Reddy; Mahima Kale R; Nallapaneni Poojitha Chowdary (Asian Journal of Medical Sciences, 2023)
Background: Size of fourth ventricle varies in different pathologies, in the context of enlarged brain ventricles size observed in routine clinical practices, knowledge of the usual range of exact measurement is required. Aims and Objectives: This study is hospital-based observational study to derive normal measurement range of fourth ventricle and correlating it with measurements of cerebrum and age of patients. Materials and Methods: Hospital-based prospective study was conducted in the department of radiodiagnosis in a teaching medical college. Patients with virtually normal study on unenhanced head CT scan of both sex and age groups from 2 year to 60 years, were included in the study. Patients with CT scans showing gross pathological changes affecting the normal anatomy of ventricles were excluded from the study. Results: The mean age of the cases was 37.0±16.88 years. Mean fourth ventricle anterioposterior dimension is 7.5±2.5 mm and transverse dimension is 12±3.1 mm. Anteroposterior diameter of fourth ventricle showed non-significant correlation (r=0.06, P=0.56) with anteroposterior diameter of skull and no significant correlation with (r=0.07, P=0.45) transverse diameter (TD) of skull. AP diameter of fourth ventricle showed a positive correlation with age, which was statistically significant (r2=0.698, P=0.01). TD of fourth ventricle showed slight positive correlation (r=0.202 P=0.048) with anteroposterior diameter of skull and (r=0.142, P=0.168) TD of skull whereas nil with. TD of fourth ventricle showed a positive correlation with age, which was statistically non-significant (r2=0.659, P=0.01). It increases with age. Conclusion: Knowledge of normal measurements helps in assessing, dilated fourth ventricle in various pathologies.